Implementation of POAC Managerial Functions in Building Santri’s Religious Character in Islamic Boarding Schools in the Era of Globalization - Ramdhani, Deden; Taufiq, Muhammad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Pesantren in the era of globalization face great challenges in maintaining the religious character of students in the midst of the swift flow of modernization. Pondok Pesantren Bahrul Hidayah Sidoarjo as one of the traditional Islamic boarding schools tries to integrate Islamic values with the demands of the times through the POAC management approach (Planning, Organizing, Actuating, Controlling). This study aims to analyze the implementation of POAC management in developing the religious character of students and identifying supporting and inhibiting factors in the implementation process. This research uses a qualitative approach with a case study method. Data were collected through participatory observation for 3 months, in-depth interviews with 12 informants (caregivers, ustadz, and santri), and document analysis. Data were analyzed interactively through data reduction, data presentation, and conclusion verification. The results showed that the implementation of POAC management at Pondok Pesantren Bahrul Hidayah Sidoarjo runs effectively through Planning: Structured program preparation such as tahajud congregation and yellow book studies. Organizing: Clear division of tasks between the fields of education, religion, and independence. Actuating: Implementation of mentoring system and exemplary by ustadz. Controlling: Monthly evaluation through muhasabah and monitoring of santri behavior. This research contributes a model of implementing POAC management contextualized with pesantren culture, as well as offering practical strategies for Islamic educational institutions in facing the challenges of globalization without losing religious identity.